Fundamentals of Entrepreneurship (ENT300) : Inteligent Tuition Centre / Aidan Newman ... [et al.] - Newman, Aidan; Maraun, Helmon; Bujang, Shalley; Ajun, Pauline; Kipperawi, Nur Nadeera (2015)
Intelligent Tuition Center is a partnership aimed to provide the customers with teaching service. There are four members of this company partnership which consist of Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The major objectives of our company are to ensure good quality of teaching service and to ensure reasonable price for the best teaching service. Intelligent Tuition Center is more focused on the satisfaction of the customers. In that case, we make sure that our services that we provide satisfy the customer where we make sure that they nbsorb the knowledge we teach effectively. We also guide our customers on how to study effectively so that they can apply these skills for future use. In order to makes our business run and progress smoothly every shareholders play their part in making this business successful. Every team members are responsible to do their work according to their expertise which will enable their task to works better. It is important for every member does their work in progress and systematically to lead the company in gaining more profit, retain and attract more customers to our tuition center. After gone through many stages of research and analysis, we find out that Batu Kawa area has a great potential to be explore. It is strategic places for us to set up our tuition center there because that particular area will be an opportunity for us since there are four main secondary school which are SMK Batu Kawa, SMK Jalan Arang, SMK Green Road and SMS Sunny Hill. There are also a lot of housing estates where they may tend to enjoy our services anytime they want because we are located near to them.